Evaluating information content of online shopping website using mouse tracker / Mutraffin Abdul Razak - Abdul Razak, Mutraffin (2013)
Nowadays people tend to shop goods and services through online as they provide the easiest way to compare products and services, save time and money and also can purchase products during sales and discounts. As the number of internet users increased, there are a bundle of online shopping websites has been developed. Despite the goodness of having various online shopping websites (OSW), there are reports made by the consumer stated that there are having problems with the information content in online shopping websites. They claimed that there is insufficient, incorrect and confusing information on the website. The purpose of this research is to evaluate the information content and design of the online shopping website using mouse tracker. During this project, usability testing has been conducted to evaluate the information content and design of Best Buy Malaysia website.LogSquare mouse tracker has been used to evaluate the participants' behavior as it can records the mouse activities in terms of video and log file. As a result, it is proven that the website faced design problems, lack and confusing information. By analyzing the data collected from the usability test and interviews of the participants, a list of recommendation on the design and information content of a website has been proposed. This result can help practitioners and web developers clarify a structured way to organize information content and identify important information cues that can be put on the websites. This research can be further expand by evaluating several online shopping websites and develop a prototype that reflects the recommendations made from this project.